2021
DOI: 10.1101/2021.11.22.469581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanically induced nuclear shuttling of β-catenin requires co-transfer of actin

Abstract: Mesenchymal stem cells (MSC) respond to environmental forces with both cytoskeletal re-structuring and activation of protein chaperones of mechanical information, β-catenin and Yes-Associated Protein 1 (YAP1). To function, MSCs must differentiate between dynamic forces such as cyclic strains of extracellular matrix due to physical activity and static strains due to ECM stiffening. To delineate how MSCs recognize and respond differently to both force types, we compared effects of dynamic (200 cycles x 2%) and s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Our results provide additional evidence along with the study by the Mauck group that showed 3% strain and 1 Hz frequency cyclic stretching induced YAP nuclear transport in MSCs (Driscoll et al, 2015). A recent report from the Rubin's group showing a contrasting result-no YAP nuclear import in MSCs under cyclic stretching at 2% strain and 10 cycles/min (or 0.167 Hz) (Sen et al, 2022) suggests that either strain or frequency, or their combination, may affect YAP nuclear transport behavior under cyclic stretch loading. While these studies from Mauck and Rubin groups did not test the role of YAP on MSC osteogenic transcription, our results may suggest an implication for bone tissue engineering and skeletal regenerative medicine.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results provide additional evidence along with the study by the Mauck group that showed 3% strain and 1 Hz frequency cyclic stretching induced YAP nuclear transport in MSCs (Driscoll et al, 2015). A recent report from the Rubin's group showing a contrasting result-no YAP nuclear import in MSCs under cyclic stretching at 2% strain and 10 cycles/min (or 0.167 Hz) (Sen et al, 2022) suggests that either strain or frequency, or their combination, may affect YAP nuclear transport behavior under cyclic stretch loading. While these studies from Mauck and Rubin groups did not test the role of YAP on MSC osteogenic transcription, our results may suggest an implication for bone tissue engineering and skeletal regenerative medicine.…”
Section: Discussionsupporting
confidence: 76%
“…Robert Mauck's group showed that YAP nuclear transport was activated by cyclic stretching at 3% strain and 1 Hz frequency (Driscoll et al, 2015). On the other hand, Janet Rubin's group reported that cyclic stretching at 2% strain and 10 cycles/min did not induce YAP nuclear import (Sen et al, 2022). However, these two studies, both of which examined bone marrow MSCs, did not test the impact of YAP on MSC osteogenic transcription and differentiation.…”
mentioning
confidence: 99%